Ethical and social marketing in Asia incorporating fairness management - Nguyen, Bang; Rowley, Chris 1959- (Elsevier, 2015)
There is a growing interest in firms' adoption of ethical and social marketing approaches among academics and practitioners alike. Ethical Marketing is the application of ethics into the marketing process, and Social Marketing is a concept that seeks to influence a target audience for the greater social good. Ethical and Social Marketing in Asia examines this so-far unexplored area, investigating why differing cultures and consumption behaviours require different emphasis in different markets. The diversity of the Asian countries provides a perplexing environment to the development and management of ethical and social marketing. The belief that bottom line profits is enough for a company, is often not favourably viewed by Asian countries emphasising collective, social and long term benefits for the people and country. Due to these interesting characteristics and complexities, the study of ethical and social marketing in Asia is a timely topic. The first chapters introduce Ethical Marketing in Asia, followed by case studies of how the approach is used across 14 diverse economies, geographically based on 'clusters'; North East, (China, Taiwan, Japan, South Korea), South East (Singapore, Malaysia, Thailand, Vietnam, Cambodia, the Philippines, Indonesia) and South Asia (India, Pakistan, Bangladesh). The second part discusses Social Marketing using the same sequence of regions and economies and the third part explores the unique link to Fairness Management in Asia, followed by a conclusion
Includes bibliographical references and index
Keywords: BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Export marketing / Moral and ethical aspects; Marketing; Marketing / Moral and ethical aspects; Social marketing; Ethik; Wirtschaft; Export marketing -- Moral and ethical aspects -- Asia; Marketing -- Asia; Marketing -- Moral and ethical aspects -- Asia; Social marketing -- Asia; Internationaler Vergleich; Wirtschaftsethik; Soziomarketing; Asien